The Effectiveness of Integrated Natural Science Learning by Using Scientific Approach-Based Module to Improve Students’ Creative Thinking Skill - Karmiatun, Dewi; Odja, Abdul Haris (International Journal of Active Learning, 2019)
The research aimed to investigate the effectiveness of integrated Natural Science learning by using a scientific approach-based module to improve students? creative thinking Skill at substance pressure concept. The module was developed by employing a 4D model by Thiagarajan, Semmel & Semmel (1974) with one group pretest-posttest design. The research involved 30 students at SMP Negeri 2 Luwuk, particularly in class VIII A2 and its instrument was creative thinking skill test adopted and composed from a test developed by Hu, Weiping (2002) and Panjaitan (2014). The instrument comprised 3 indicators which were thinking fluency, thinking flexibility, and thinking originality. It used average normalized gain as analysis. The finding of research showed that the result of the normalized N-gain test differed in each of creative thinking indicator. The values of N-gain for an aspect of fluency was 0.58 with a medium category, for an aspect of flexibility was 0.57 with medium category and for an aspect of originality was 0.13 with a low category. In brief, the average value of N-gain for all creative thinking indicators was 0.42 with a medium category. To conclude, the finding confirmed that the integrated Natural Science learning by using scientific approach-based module was effective in improving students? creative thinking skill at substance pressure concept.